Site-Specific Sequence Exchange Between Homologous and Non-homologous Chromosomes - Yin, Qian; Li, Ruyu; Ow, David W. (Frontiers in Plant Science, 2022)
Transgene integration typically takes place in an easy-to-transform laboratory variety before the transformation event is introgressed through backcrosses to elite cultivars. As new traits are added to existing transgenic lines, site-specific integration can stack new transgenes into a previously-created transgenic locus. In planta site-specific integration minimizes the number of segregating loci to assemble into a breeding line, but cannot break genetic linkage between the transgenic locus and nearby undesirable traits. Here, we describe an additional feature of an in planta gene stacking scheme, in which the Cre recombinase not only deletes transgenic DNA no longer needed after transformation, but also mediates recombination between homologous or non-homologous chromosomes. Although the target site must first be introgressed through conventional breeding, subsequent transgenes inserted into the same locus would be able to use Cre-mediated translocation to expedite a linkage drag-free introgression to field cultivars.